Tenofovir diphosphate is a poor substrate and a weak inhibitor of rat DNA polymerases alpha, delta, and epsilon* - Birkus, Gabriel; Hájek, Miroslav; Kramata, Pavel; Votruba, Ivan; Holý, Antonín; Otová, Berta (Antimicrobial agents and chemotherapy, 2002)
Tenofovir diphosphate (PMPApp) is a weak inhibitor of DNA polymerases (pol) alpha, delta, and epsilon*, with values for the Ki for PMPApp ((PMPApp)Ki) relative to the Km for dATP ((dATP)Km) of 10.2, 10.2, and 15.2, respectively. Its incorporation into DNA was about 1,000-fold less efficient than that of dATP, with (PMPApp)Km values 350-, 2,155-, and 187-fold higher than (dATP)Km values for pol alpha, delta, and epsilon*, respectively.
Keywords: DNA-dependentní DNA-polymerasy; Adenine; Anti-HIV Agents; DNA-polymerasa I; organofosfonáty; DNA Polymerase III; organofosforové sloučeniny; Reverse Transcriptase Inhibitors; inhibitory syntézy nukleových kyselin; krysa rodu Rattus; DNA-Directed DNA Polymerase; zvířata; DNA Polymerase II; inhibitory reverzní transkriptasy; DNA Polymerase I; adenin; Organophosphorus Compounds; látky proti HIV; Rats; tenofovir; Organophosphonates; Animals; DNA-polymerasa II; DNA-polymerasa III; Tenofovir; Nucleic Acid Synthesis Inhibitors